A semi-prefabricated plastic track foam roll
By using grafting reactions of hindered amines and phosphorus-based flame retardants in plastic runway materials, a flame retardant containing hindered phenols and hindered amines is generated, which solves the problem of aging and degradation of plastic runway materials and achieves higher flame retardant and anti-aging properties.
Patent Information
- Application Number
- CN202411754918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Existing plastic runway materials are prone to aging and degradation when exposed to external environments for a long time, resulting in performance degradation.
Using a semi-prefabricated plastic runway foaming coil, the hindered amine 4-amino-2,2,6,6-tetramethylpiperidine and parahydroxybenzaldehyde were used to form Schiff base, and grafted with 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide to form a flame retardant containing hindered phenol and hindered amine, which was added to polyurethane to improve flame retardant and anti-aging properties.
It significantly improves the flame retardant and anti-aging properties of the plastic runway, extends the service life of the material, and enhances its stable performance under different weather conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic runways, in particular to a semi-prefabricated plastic runway foaming coil. Background Art
[0002] Synthetic track is one of the most widely used track surface materials. It is made of specific granular materials and adhesives. These granular materials give the track excellent elasticity, durability and anti-slip properties, which can effectively absorb the impact during exercise and provide good cushioning for athletes, thereby protecting their joints and ligaments and reducing the risk of sports injuries. The adhesive not only tightly combines these particles into a whole, but also enhances the wear resistance and environmental adaptability of the track, ensuring that the track can maintain stable performance under different weather conditions and extend its service life.
[0003] However, since the runway material is in the external environment for a long time, the polymer will age and degrade, and its performance will also decay accordingly; therefore, there is an urgent need to provide a plastic runway foam roll with excellent anti-aging properties. Summary of the invention
[0004] The purpose of the present invention is to provide a semi-prefabricated plastic track foam coiled material to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A semi-prefabricated plastic track foam coil comprises the following preparation steps:
[0007] S1. Weigh castor oil, polyether glycol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and modified flame retardant according to a mass ratio of 35-40:4.5-7.5:2.5-3:2.2-2.5:1.2-1.8, and stir and mix them evenly. After stirring, stir at a temperature of 90-100° C. and a pressure of -0.1 MPa for 35-45 minutes, then cool to 45-55° C. to prepare component A, and seal and store for standby use;
[0008] S2. Weigh polyether triol and diphenylmethane diisocyanate in a mass ratio of 5.5-6:1, stir evenly, heat to 80-85°C, keep warm for 85-95 minutes, then add dibutyltin dilaurate in an amount of 0.015%-0.02% times the mass of diphenylmethane diisocyanate, stir for 20-25 minutes, prepare component B, and seal and store for later use;
[0009] S3, mixing component A and component B at a mass ratio of 1:1-1.2, adding waste rubber particles 1.8-2.2 times the mass of component A, stirring evenly, pressing and curing to prepare a foaming precursor, and molding and foaming the foaming precursor to prepare a foaming coil;
[0010] Preferably, the modified flame retardant comprises the following preparation steps: adding the grafted flame retardant to chloroform with a mass of 20 to 22 times that of the grafted flame retardant, stirring evenly, and preparing a grafted flame retardant solution; then, at a temperature of 0 to 5°C, dropping the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution into the grafted flame retardant solution with a mass of 0.85 to 0.9 times that of the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution at a rate of 0.5 mL / min, and simultaneously dropping the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution at a rate of 0.3 mL / min. The triethylamine solution is added dropwise to the grafted flame retardant solution which is 2 to 2.2 times the mass of the triethylamine solution. After the addition is completed, stir for 30 to 35 minutes. After the stirring is completed, heat to 35 to 45°C and react for 22 to 26 hours. After the reaction is completed, remove the solvent by rotary evaporation at a temperature of 55 to 65°C. After the rotary evaporation is completed, add 40 to 45 times the mass of the grafted flame retardant in glacial ether, stir to precipitate a white precipitate, let it stand until the precipitation is complete, filter under reduced pressure, and wash the filtered product with glacial ether for 3 to 5 times. After washing, place it at 25 to 30°C and vacuum dry it for 12 to 14 hours to obtain a modified flame retardant.
[0011] Preferably, the compression foaming comprises the following preparation steps: placing a foaming precursor into a compression foaming cavity, controlling the temperature in the molding machine mold at 130-140°C, the pressure of the supercritical fluid at 10-12 MPa, and then foaming at a constant temperature and pressure for 3-3.5 hours, and releasing the pressure to normal pressure after foaming is completed.
[0012] Preferably, the supercritical fluid is carbon dioxide.
[0013] Preferably, the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution comprises the following preparation steps: adding 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride to chloroform in an amount 30 to 32 times the mass of 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride, stirring evenly, and preparing a 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution for standby use.
[0014] Preferably, the triethylamine solution comprises the following preparation steps: adding triethylamine to chloroform with a mass 10 to 12 times that of the triethylamine, stirring evenly, and preparing a triethylamine solution for standby use.
[0015] Preferably, the grafted flame retardant comprises the following preparation steps: adding p-hydroxybenzaldehyde to anhydrous ethanol with a mass of 14 to 15 times that of p-hydroxybenzaldehyde, stirring evenly, and preparing a p-hydroxybenzaldehyde solution; then uniformly dropping a 4-amino-2,2,6,6-tetramethylpiperidine solution into a p-hydroxybenzaldehyde solution with a mass of 1.8 to 2 times that of the 4-amino-2,2,6,6-tetramethylpiperidine solution at a rate of 0.4 mL / min, and after the dropping is completed, heating to 45 to 55 °C and stirring for 2 to 2.5 hours. After stirring, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in an amount of 1.5 to 1.8 times the mass of p-hydroxybenzaldehyde. After adding, heat to 75 to 85°C and stir for 8 to 8.5 hours. After stirring, cool to 25 to 30°C, filter and wash the filtered product with anhydrous ethanol and deionized water for 2 to 3 times respectively. After washing, vacuum dry at 55 to 65°C for 24 to 30 hours to obtain a grafted flame retardant.
[0016] Preferably, the 4-amino-2,2,6,6-tetramethylpiperidine solution comprises the following preparation steps: adding 4-amino-2,2,6,6-tetramethylpiperidine to anhydrous ethanol with a mass of 4 to 5 times that of 4-amino-2,2,6,6-tetramethylpiperidine, stirring evenly, and preparing a 4-amino-2,2,6,6-tetramethylpiperidine solution for standby use.
[0017] Preferably, the nanoparticles are nano-titanium dioxide.
[0018] Preferably, the average particle size of the nanoparticles is between 100 and 200 nm.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The plastic track of the present application is mainly developed from waste rubber particles and polyurethane. Although the polyurethane material itself, as a processed polymer material with good comprehensive performance, has a lot of advantages as a track material, since the track material is in the external environment for a long time, it will cause the polymer to age and degrade, and its performance will also decay accordingly. Therefore, the present application uses hindered amine 4-amino-2,2,6,6-tetramethylpiperidine to react with the aldehyde group of p-hydroxybenzaldehyde to generate a Schiff base containing a piperidine ring, and grafts it with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and then through the reaction of hindered phenol 3,5-bis (tert-butyl) -4-hydroxyphenylpropionyl chloride with the hydroxyl group of p-hydroxybenzaldehyde, a flame retardant containing both hindered phenol and hindered amine is generated. By adding the flame retardant to the polyurethane, the flame retardant performance of the plastic track is improved on the one hand, and the anti-aging performance of the plastic track is also improved on the other hand;
[0021] On the one hand, traditional hindered phenol antioxidants are widely used due to their light color, low toxicity and high aging resistance, but they are usually low molecular weight, resulting in poor thermal stability, high volatility and poor migration resistance. Therefore, by grafting them with flame retardants, their thermal stability is greatly improved and the increase in molecular weight makes them less likely to precipitate. At the same time, the grafted hindered amines can inhibit photo-oxidative degradation reactions through multiple pathways such as capturing free radicals, decomposing hydroperoxides and transferring the energy of excited molecules. They can also form intramolecular synergistic effects with hindered phenols, greatly improving the anti-aging performance of plastic tracks.
[0022] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is a phosphorus-based flame retardant with good flame retardant and heat resistance. The grafted hindered amines during the flame retardant process can also exert the free radical quenching effect of hindered amines to inhibit the continuous combustion of combustible gases. Phosphorus-based flame retardants can effectively improve the flame retardant properties of plastic tracks by synergizing with the N element in hindered amines. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] S1, p-hydroxybenzaldehyde is added to anhydrous ethanol with a mass of 14 times that of p-hydroxybenzaldehyde, and stirred evenly to prepare a p-hydroxybenzaldehyde solution; then, 4-amino-2,2,6,6-tetramethylpiperidine solution is uniformly added dropwise to p-hydroxybenzaldehyde solution with a mass of 1.8 times that of 4-amino-2,2,6,6-tetramethylpiperidine solution at a rate of 0.4 mL / min, after the addition is complete, the temperature is raised to 45 ° C and stirred for 2 h, after the stirring is complete, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a mass of 1.5 times that of p-hydroxybenzaldehyde is added, and the addition is complete. After completion, the temperature is raised to 75°C, stirred for 8 hours, cooled to 25°C after stirring, filtered, and the filtered product is washed twice with anhydrous ethanol and deionized water respectively, and after washing, vacuum dried at a temperature of 55°C for 24 hours to obtain a grafted flame retardant; the 4-amino-2,2,6,6-tetramethylpiperidine solution comprises the following preparation steps: adding 4-amino-2,2,6,6-tetramethylpiperidine to anhydrous ethanol with a mass of 4 times that of 4-amino-2,2,6,6-tetramethylpiperidine, stirring evenly, and preparing a 4-amino-2,2,6,6-tetramethylpiperidine solution for standby use;
[0026] S2. Add the grafted flame retardant to chloroform with a mass of 20 times that of the grafted flame retardant, stir evenly, and prepare a grafted flame retardant solution; then, at a temperature of 0°C, add 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution to a grafted flame retardant solution with a mass of 0.85 times that of the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution at a rate of 0.5 mL / min, and while adding the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution, simultaneously add triethylamine solution to a grafted flame retardant solution with a mass of 2 times that of the triethylamine solution at a rate of 0.3 mL / min. After the addition is complete, stir for 30 minutes, heat to 35°C after stirring, and then react for 22 hours. After the reaction is complete, remove the solvent by rotary evaporation at a temperature of 55°C, and then rotary After the evaporation is completed, 40 times the mass of the grafted flame retardant is added with glacial ether, stirred to precipitate a white precipitate, and after standing for complete precipitation, the precipitate is filtered under reduced pressure, and the filtered product is washed with glacial ether for 3 times. After washing, it is placed at 25°C and vacuum dried for 12 hours to obtain a modified flame retardant. The 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution includes the following preparation steps: 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride is added to 30-32 times the mass of chloroform of 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride, stirred evenly, and prepared into a 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution for standby use; the triethylamine solution includes the following preparation steps: triethylamine is added to 10 times the mass of triethylamine in chloroform, stirred evenly, and prepared into a triethylamine solution for standby use;
[0027] S3, weighing castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and modified flame retardant according to a mass ratio of 35:4.5:2.5:2.2:1.2, and stirring and mixing them evenly, stirring at a temperature of 90°C and a pressure of -0.1MPa for 35 minutes, then cooling to 45°C to prepare component A, and sealing and storing for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 100nm;
[0028] S4, weighing polyether triol and diphenylmethane diisocyanate in a mass ratio of 5.5:1, stirring evenly, heating to 80°C, keeping the temperature for reaction for 85 minutes, then adding dibutyltin dilaurate at a mass ratio of 0.015% of diphenylmethane diisocyanate, stirring for 20 minutes, preparing component B, and sealing and storing for later use;
[0029] S5. Mix component A and component B in a mass ratio of 1:1 and stir evenly, add waste rubber particles 1.8 times the mass of component A, stir evenly and solidify on a press plate to prepare a foaming precursor, and perform compression foaming on the foaming precursor to prepare a foaming coil; the compression foaming includes the following preparation steps: put the foaming precursor into a compression foaming cavity, control the temperature in the molding machine mold at 130°C, the pressure of the supercritical fluid is 10MPa, then foam at a constant temperature and pressure for 3 hours, and release the pressure to normal pressure after the foaming is completed; the supercritical fluid is carbon dioxide.
[0030] Example 2
[0031] S1. Add p-hydroxybenzaldehyde to anhydrous ethanol with a mass of 15 times that of p-hydroxybenzaldehyde, stir evenly, and prepare a p-hydroxybenzaldehyde solution; then uniformly add 4-amino-2,2,6,6-tetramethylpiperidine solution to p-hydroxybenzaldehyde solution with a mass of 1.9 times that of 4-amino-2,2,6,6-tetramethylpiperidine solution at a rate of 0.4 mL / min, after the addition is complete, heat to 50°C and stir for 2.5 h, after the stirring is complete, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a mass of 1.7 times that of p-hydroxybenzaldehyde, and add until complete. The mixture was heated to 8°C and stirred for 8.5 hours. After stirring, the mixture was cooled to 25°C, filtered, and the filtered product was washed three times with anhydrous ethanol and deionized water respectively. After washing, the mixture was vacuum dried for 28 hours at 60°C to obtain a grafted flame retardant. The 4-amino-2,2,6,6-tetramethylpiperidine solution comprises the following preparation steps: adding 4-amino-2,2,6,6-tetramethylpiperidine to anhydrous ethanol with a mass of 4.5 times that of 4-amino-2,2,6,6-tetramethylpiperidine, stirring evenly, and preparing a 4-amino-2,2,6,6-tetramethylpiperidine solution for standby use.
[0032] S2. Add the grafted flame retardant to chloroform with a mass of 21 times that of the grafted flame retardant, stir evenly, and prepare a grafted flame retardant solution; then, at a temperature of 0°C, add the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution to the grafted flame retardant solution with a mass of 0.88 times that of the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution at a rate of 0.5 mL / min, and while adding the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution, simultaneously add the triethylamine solution to the grafted flame retardant solution with a mass of 2.1 times that of the triethylamine solution at a rate of 0.3 mL / min. After the addition is completed, stir for 32 minutes, raise the temperature to 35-45°C after the stirring is completed, and then react for 24 hours. After the reaction is completed, rotary evaporate and remove at a temperature of 60°C. Solvent, after rotary evaporation, add 42 times the mass of grafted flame retardant glacial ether, stir to precipitate white precipitate, stand for precipitation, filter under reduced pressure, wash the filtered product with glacial ether 4 times, place under 25°C and vacuum dry for 12 hours after washing to obtain modified flame retardant; 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution includes the following preparation steps: add 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride to 31 times the mass of 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride in chloroform, stir evenly, prepare 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution for standby; triethylamine solution includes the following preparation steps: add triethylamine to 11 times the mass of triethylamine in chloroform, stir evenly, prepare triethylamine solution for standby;
[0033] S3, weighing castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and modified flame retardant in a mass ratio of 37:6:2.5-3:2.3:1.6, and stirring and mixing them evenly, stirring at a temperature of 100°C and a pressure of -0.1MPa for 40 minutes, then cooling to 50°C to prepare component A, and sealing and storing for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 150nm;
[0034] S4, weighing polyether triol and diphenylmethane diisocyanate in a mass ratio of 5.8:1, stirring evenly, heating to 80°C, keeping the temperature for reaction for 90 minutes, then adding dibutyltin dilaurate at a mass ratio of 0.018% of diphenylmethane diisocyanate, stirring for 25 minutes, preparing component B, and sealing and storing for later use;
[0035] S5. Mix component A and component B in a mass ratio of 1:1.1 and stir evenly, add waste rubber particles twice the mass of component A, stir evenly and solidify on a press plate to prepare a foaming precursor, and perform compression foaming on the foaming precursor to prepare a foaming coil; the compression foaming includes the following preparation steps: put the foaming precursor into a compression foaming cavity, control the temperature in the mold of the compression molding machine at 135°C, the pressure of the supercritical fluid at 12MPa, then foam at a constant temperature and pressure for 3.5 hours, and release the pressure to normal pressure after the foaming is completed; the supercritical fluid is carbon dioxide.
[0036] Example 3
[0037] S1, p-hydroxybenzaldehyde is added to anhydrous ethanol with a mass of 15 times that of p-hydroxybenzaldehyde, and stirred evenly to prepare a p-hydroxybenzaldehyde solution; then, 4-amino-2,2,6,6-tetramethylpiperidine solution is uniformly added dropwise to p-hydroxybenzaldehyde solution with a mass of 2 times that of 4-amino-2,2,6,6-tetramethylpiperidine solution at a rate of 0.4 mL / min, after the addition is complete, the temperature is raised to 55 ° C and stirred for 2.5 h, after the stirring is complete, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a mass of 1.8 times that of p-hydroxybenzaldehyde is added, and the addition is complete. The mixture was heated to 85°C and stirred for 8.5 hours. After stirring, the mixture was cooled to 30°C, filtered, and the filtered product was washed three times with anhydrous ethanol and deionized water respectively. After washing, the mixture was vacuum dried for 30 hours at a temperature of 65°C to obtain a grafted flame retardant. The 4-amino-2,2,6,6-tetramethylpiperidine solution comprises the following preparation steps: adding 4-amino-2,2,6,6-tetramethylpiperidine to anhydrous ethanol with a mass of 5 times that of 4-amino-2,2,6,6-tetramethylpiperidine, stirring evenly, and preparing a 4-amino-2,2,6,6-tetramethylpiperidine solution for standby use.
[0038] S2. Add the grafted flame retardant to chloroform with a mass of 22 times that of the grafted flame retardant, stir evenly, and prepare a grafted flame retardant solution; then, at a temperature of 5°C, add the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution dropwise to the grafted flame retardant solution with a mass of 0.9 times that of the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution at a rate of 0.5 mL / min, and while adding the 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution dropwise, simultaneously add the triethylamine solution dropwise to the grafted flame retardant solution with a mass of 2.2 times that of the triethylamine solution at a rate of 0.3 mL / min. After the addition is completed, stir for 35 minutes, heat to 45°C after the stirring is completed, and then react for 26 hours. After the reaction is completed, remove the solvent by rotary evaporation at a temperature of 65°C. After rotary evaporation, add 45 times the mass of the grafted flame retardant in glacial ether, stir to precipitate a white precipitate, stand for precipitation, filter under reduced pressure, and wash the filtered product with glacial ether 5 times. After washing, place it at 30°C and vacuum dry it for 14 hours to obtain a modified flame retardant; the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution includes the following preparation steps: add 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride to 32 times the mass of 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride in chloroform, stir evenly, and prepare a 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution for standby use; the triethylamine solution includes the following preparation steps: add triethylamine to 12 times the mass of triethylamine in chloroform, stir evenly, and prepare a triethylamine solution for standby use;
[0039] S3, weighing castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and modified flame retardant according to a mass ratio of 40:7.5:3:2.5:1.8, and stirring and mixing evenly, stirring at a temperature of 100°C and a pressure of -0.1MPa for 45 minutes, then cooling to 55°C to prepare component A, and sealing and storing for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 200nm;
[0040] S4, weighing polyether triol and diphenylmethane diisocyanate in a mass ratio of 6:1, stirring evenly, heating to 85°C, keeping the temperature for reaction for 95 minutes, then adding dibutyltin dilaurate at a mass ratio of 0.02% of diphenylmethane diisocyanate, stirring for 25 minutes, preparing component B, and sealing and storing for later use;
[0041] S5. Mix component A and component B in a mass ratio of 1:1.2 and stir evenly, add waste rubber particles 2.2 times the mass of component A, stir evenly and solidify on a press plate to prepare a foaming precursor, and perform compression foaming on the foaming precursor to prepare a foaming coil; the compression foaming includes the following preparation steps: put the foaming precursor into a compression foaming cavity, control the temperature in the molding machine mold at 140°C, the pressure of the supercritical fluid at 12MPa, then foam at a constant temperature and pressure for 3.5 hours, and release the pressure to normal pressure after foaming; the supercritical fluid is carbon dioxide.
[0042] Example 4
[0043] The difference from Example 1 is only that step S1: castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and grafted flame retardant are weighed according to a mass ratio of 35:4.5:2.5:2.2:1.2, and stirred to mix evenly. After stirring, stir at a temperature of 90° C. and a pressure of -0.1 MPa for 35 minutes, then cool to 45° C. to prepare component A, and seal and store for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 100 nm;
[0044] Example 5
[0045] The difference from Example 1 is only that step S1: castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are weighed in a mass ratio of 35:4.5:2.5:2.2:1.2, and stirred to mix evenly. After stirring, stir at a temperature of 90° C. and a pressure of -0.1 MPa for 35 minutes, then cool to 45° C. to prepare component A, and seal and store for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 100 nm;
[0046] Example 6
[0047] The difference from Example 1 is only that step S1: castor oil, polyether diol, 3,3'-dichloro-4,4'-diaminodiphenylmethane and nanoparticles are weighed in a mass ratio of 35:4.5:2.5:2.2, and stirred to mix evenly, and after stirring, stirred at a temperature of 90° C. and a pressure of -0.1 MPa for 35 minutes, then cooled to 45° C. to prepare component A, which is sealed and stored for standby use; the nanoparticles are nano titanium dioxide; the average particle size of the nanoparticles is 100 nm;
[0048] Performance test: The foamed coils prepared in the above Examples 1 to 6 were tested for mechanical properties, anti-aging properties and flame retardancy;
[0049] Mechanical properties: The tensile strength and elongation of the specimens were tested in accordance with ISO 527-1:2019;
[0050] Anti-aging performance: Place the sample in a xenon aging test chamber, irradiate ultraviolet rays of 290~340nm, the rated power is 1.8kW, the temperature is (60±3)℃, the relative humidity is (50±5)%, and the ultraviolet aging time is 200h; after the sample is aged, the tensile strength performance test is performed again according to the above-mentioned tensile strength test method and compared with the previous tensile strength test data;
[0051] The calculation formula is: Anti-aging performance = tensile strength after aging / tensile strength before aging × %
[0052] Flame retardant performance: Refer to ASTM D3801-2020 and use a horizontal vertical combustion tester to test the flame retardant performance of the sample;
[0053] Table 1 Experimental data of mechanical properties, anti-aging properties and flame retardant properties
[0054]
[0055] From the comparison of the experimental data in Table 1, it can be found that Examples 1 to 3 all maintain good performance and are much higher than Examples 4 to 6. In Examples 4 to 6, it can be expected that the performance and indicators thereof will decline, mainly because in Example 4, a grafted flame retardant is used as a flame retardant for addition, and only a hindered amine is grafted as an anti-aging agent, resulting in a rapid decline in its anti-aging performance, but its flame retardant performance remains good, mainly because the hindered amine therein and the N and P elements of (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) DOPO produce a synergistic effect, so that its flame retardant performance remains good; in Example 5, its flame retardant performance declines, mainly due to the lack of synergy, and because it does not contain any anti-aging agent, its anti-aging performance declines significantly; in Example 6, no flame retardant is added, so its various indicators are the lowest.
[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A semi-prefabricated plastic track foam coil, characterized in that: The method comprises the following preparation steps: S1. Weigh castor oil, polyether glycol, 3,3'-dichloro-4,4'-diaminodiphenylmethane, nanoparticles and modified flame retardant according to a mass ratio of 35-40:4.5-7.5:2.5-3:2.2-2.5:1.2-1.8, and stir and mix them evenly. After stirring, stir at a temperature of 90-100° C. and a pressure of -0.1 MPa for 35-45 minutes, then cool to 45-55° C. to prepare component A, and seal and store for standby use; S2. Weigh polyether triol and diphenylmethane diisocyanate in a mass ratio of 5.5-6:1, stir evenly, heat to 80-85°C, keep warm for 85-95 minutes, then add dibutyltin dilaurate in an amount of 0.015%-0.02% times the mass of diphenylmethane diisocyanate, stir for 20-25 minutes, prepare component B, and seal and store for later use; S3, mixing component A and component B at a mass ratio of 1:1-1.2, adding waste rubber particles 1.8-2.2 times the mass of component A, stirring evenly, pressing and curing to prepare a foaming precursor, and molding and foaming the foaming precursor to prepare a foaming coil; The modified flame retardant comprises the following preparation steps: adding the grafted flame retardant to chloroform with a mass of 20 to 22 times that of the grafted flame retardant, stirring evenly, and preparing a grafted flame retardant solution; Then, at a temperature of 0-5°C, the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution was added dropwise at a rate of 0.5 mL / min to a grafted flame retardant solution of 0.85-0.9 times the mass of the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution. While adding the 3,5-bis(tert-butyl)-4-hydroxybenzene propionyl chloride solution, the triethylamine solution was added dropwise at a rate of 0.3 mL / min to a grafted flame retardant solution of 2-2.2 times the mass of the triethylamine solution. After the addition was completed, After the reaction, stir for 30-35 minutes, heat to 35-45°C, and react for 22-26 hours. After the reaction, remove the solvent by rotary evaporation at 55-65°C. After the rotary evaporation, add 40-45 times the mass of the grafted flame retardant, stir to precipitate a white precipitate, stand for precipitation, and filter under reduced pressure after the precipitation is complete. Wash the filtered product with icy ether for 3-5 times. After washing, place it at 25-30°C and vacuum dry it for 12-14 hours to obtain a modified flame retardant. The grafted flame retardant comprises the following preparation steps: adding p-hydroxybenzaldehyde to anhydrous ethanol with a mass of 14 to 15 times that of the p-hydroxybenzaldehyde, stirring evenly, and preparing a p-hydroxybenzaldehyde solution; then uniformly dropping a 4-amino-2,2,6,6-tetramethylpiperidine solution into a p-hydroxybenzaldehyde solution with a mass of 1.8 to 2 times that of the 4-amino-2,2,6,6-tetramethylpiperidine solution at a speed of 0.4 mL / min, and after the dropping is completed, heating to 45 to 55° C. and stirring 2~2.5h, after stirring, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in an amount of 1.5~1.8 times the mass of p-hydroxybenzaldehyde, after adding, heat to 75~85°C, stir for 8~8.5h, after stirring, cool to 25~30°C, filter and wash the filtered product with anhydrous ethanol and deionized water for 2~3 times respectively, after washing, vacuum dry at 55~65°C for 24~30h to obtain a grafted flame retardant; The 4-amino-2,2,6,6-tetramethylpiperidine solution comprises the following preparation steps: adding 4-amino-2,2,6,6-tetramethylpiperidine to anhydrous ethanol with a mass of 4 to 5 times that of 4-amino-2,2,6,6-tetramethylpiperidine, stirring evenly, and preparing a 4-amino-2,2,6,6-tetramethylpiperidine solution for standby use.
2. The semi-prefabricated plastic track foam coil according to claim 1, characterized in that: The compression foaming comprises the following preparation steps: placing a foaming precursor into a compression foaming cavity, controlling the temperature in the compression mold of the compression molding machine to be 130-140° C., the pressure of the supercritical fluid to be 10-12 MPa, then foaming at a constant temperature and pressure for 3-3.5 hours, and releasing the pressure to normal pressure after the foaming is completed.
3. The semi-prefabricated plastic track foam coil according to claim 2, characterized in that: The supercritical fluid is carbon dioxide.
4. The semi-prefabricated plastic track foam coil according to claim 1, characterized in that: The 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution comprises the following preparation steps: adding 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride to chloroform with a mass of 30 to 32 times that of 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride, stirring evenly, and preparing a 3,5-bis(tert-butyl)-4-hydroxybenzenepropionyl chloride solution for standby use.
5. The semi-prefabricated plastic track foam coil according to claim 1, characterized in that: The triethylamine solution comprises the following preparation steps: adding triethylamine into chloroform with a mass 10 to 12 times that of the triethylamine, stirring evenly, and preparing the triethylamine solution for standby use.
6. The semi-prefabricated plastic track foam coil according to claim 1, characterized in that: The nanoparticles are nano titanium dioxide.
7. The semi-prefabricated plastic track foam coil according to claim 6, characterized in that: The average particle size of the nanoparticles is between 100 and 200 nm.
Citation Information
Patent Citations
Polyhydroxy benzene ring phosphorus-nitrogen type flame retardant, manufacturing method and application thereof in flame retardant polyurethane hard bubble material
CN108285523A
Nitrogen-phosphorus efficient flame retardant containing p-hydroxybenzaldehyde and tryptamine structures, preparation method and application
CN111303483A